2014
DOI: 10.1210/jc.2013-3488
|View full text |Cite
|
Sign up to set email alerts
|

mRNA-Binding Protein TIA-1 Reduces Cytokine Expression in Human Endometrial Stromal Cells and Is Down-Regulated in Ectopic Endometrium

Abstract: Endometrial TIA-1 is regulated throughout the menstrual cycle, TIA-1 modulates the expression of immune factors in endometrial cells, and downregulation of TIA-1 may contribute to the pathogenesis of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…These observations strengthen the association of this gene subset with most transformed cell phenotypes and relate it to cell growth and survival responses [47] , [48] . The effects of TIA expression on extracellular matrix and focal/cell adhesion phenomena would depend on how transcriptome dynamics are integrated in a given cell type and physiological context, and could have significant implications in inflammatory diseases and cancer progression [17] , [19] , [22] [25] , [49] , [50] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations strengthen the association of this gene subset with most transformed cell phenotypes and relate it to cell growth and survival responses [47] , [48] . The effects of TIA expression on extracellular matrix and focal/cell adhesion phenomena would depend on how transcriptome dynamics are integrated in a given cell type and physiological context, and could have significant implications in inflammatory diseases and cancer progression [17] , [19] , [22] [25] , [49] , [50] .…”
Section: Discussionmentioning
confidence: 99%
“…The progressive acquisition of mutations in oncogenes or tumor-suppressor genes might act in concert with epigenetic events, such as functional down-regulation of TIA proteins, to give cells a competitive growth advantage. TIA1 and TIAR genes are mutated [52] and down-regulated [18] , [21] , [25] , [44] , [49] , [50] in several types of human cancers. In human transformed cells, TIA proteins regulate the transcription, alternative splicing, stability and/or translation of many target genes associated with tumor development and progression, involving the control of cell proliferation, apoptosis, angiogenesis, invasion, metastasis, evasion of immune recognition and metabolic reprogramming [13] [25] .…”
Section: Discussionmentioning
confidence: 99%
“…106 In fact, TIA proteins can regulate/ modulate the expression of inflammatory proteins such as TNFa, IL-1, IL-6, MMP13 or COX-2. 5,16,51,52,54,[107][108][109] For example, in women with endometriosis, TIA1 expression in eutopic and ectopic endometrium was reduced compared with TIA1 expression in eutopic endometrium of unaffected control women. Lipopolysaccharide and TNF-a increased TIA1 expression in human endometrial stromal cells (HESCs) in vitro, whereas IL-6 or steroid hormones had no effect.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Thus, endometrial TIA1 is regulated throughout the menstrual cycle, TIA1 modulates the expression of immune factors in endometrial cells, and downregulation of TIA1 may contribute to the pathogenesis of endometriosis. 109 Regarding cytotoxicity mediated by TIA proteins and, in particular, TIA1 as a component of cytotoxic T lymphocyte granules, there are several reports describing that apoptosis mediated by cytotoxic T-lymphocytes provokes the onset of a series of reactions that are uncomfortable for the patient such as, for example, organ transplant rejection, 110,111 food allergy, 112 Crohn's disease and ulcerative colitis, 113 aplastic anemia 114 or platelet inhibition. 115 However, an increase in cytotoxic T-lymphocytes is not always negative; it has been demonstrated that a higher percentage of infiltrated CD8C T cells is associated with better prognosis in cancer patients, suggesting a role for CD8C T lymphocytes in the anti-tumoral response.…”
Section: Viral Infectionsmentioning
confidence: 99%
“…It is a chronic disease and a clinical problem in women of fertile age, with a high impact on quality of life, work productivity and health care management (1-2-3-4). The ectopic endometrial tissue responds to steroid hormones and drugs even if the response to hormones may be different from that of eutopic endometrium (5-6-7-8). Endometriosis is estimated to affect from 5% to 45% of women of reproductive age (9).…”
Section: Introductionmentioning
confidence: 99%